Analisis Komparatif Mutu Produk dan Korelasi Kualitas Pelayanan terhadap Kepuasan Pasien: Sebuah Studi Biostatistik - La Jisi, Wulandari; Sri Wahyuni (Jurnal Medicare, 2026)
This study aims to analyze two different domains through a biostatistical approach: the relationship between service quality and patient satisfaction at Health Center X, and the comparative quality of life span among three battery brands (A, B, and C) produced by PT Sinar Terang. The research method used is quantitative, with a sample of 15 respondents for the correlation test and 24 battery units for the comparative test. Data were analyzed using statistical software with Spearman’s rho correlation and the Kruskal-Wallis non-parametric test, as heterogeneity of variance was found in the industrial data (Sig. 0.000). The results showed a positive and significant relationship between service quality and patient satisfaction (r = 0.591; Sig. = 0.020). In the industrial domain, a significant difference in product quality was found among the three battery brands (Sig. = 0.033). The conclusion of this study confirms that service quality is a primary determinant of patient satisfaction, while quality variability in manufactured products requires stricter production line standardization to ensure quality consistency.